A study of gamma-ray scattering by semi-infinite media as applied to the 'Hidrodensimeter' density gauge - Curtayne, Peter C.(Peter Charles) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1967.